2021
DOI: 10.1124/dmd.120.000318
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Physiologically Based Pharmacokinetic Modeling and Experimental Data to Guide Dosing Modification of CYP3A-Mediated Drug-Drug Interactions in the Pediatric Population

Abstract: A inactivator , enzymatic activity of the inactivator; A vehicle , enzymatic activity of the vehicle control; AAG, alpha-1 acid glycoprotein; AFE, average fold error; AUC, area under the concentration versus time curve; AUC 0-∞, area under the concentration versus time curve extrapolated to infinity; AUC 0-τ, area under the concentration versus time curve within a dosing interval; AUC 0-8 , area under the concentration versus time curve from 0 to 8 hours; AUC 0-24,ss , area under the concentration versus time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Apart from changes in the physiology and anatomy, the pediatric model accounted for the ontogeny of CYP3A4, CYP1A2, and CYP2C8. While CYP3A reaches adult levels at 1 year of life, CYP1A2 takes longer to mature 32 . Simulations were performed using the pediatric model with the approved recommended pediatric dose of 230 mg/m 2 twice daily.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from changes in the physiology and anatomy, the pediatric model accounted for the ontogeny of CYP3A4, CYP1A2, and CYP2C8. While CYP3A reaches adult levels at 1 year of life, CYP1A2 takes longer to mature 32 . Simulations were performed using the pediatric model with the approved recommended pediatric dose of 230 mg/m 2 twice daily.…”
Section: Discussionmentioning
confidence: 99%
“…While CYP3A reaches adult levels at 1 year of life, CYP1A2 takes longer to mature. 32 Simulations were performed using the pediatric model with the approved recommended pediatric dose of 230 mg/m 2 twice daily. While the pediatric model successfully predicted nilotinib PK for the older age groups of the 2 clinical studies used for model evaluation (6-12 and 12-18 years from Heimbach et al 12 and 10-18 years from Hijiya et al 18 ), it overestimated nilotinib exposure in the lowest age groups of these 2 clinical studies (2-6 and 1-10 years old as reported by Heimbach et al 12 and Hijiya et al 18 , respectively).…”
Section: Discussionmentioning
confidence: 99%
“…With the majority of clinical DDI studies being conducted in healthy volunteers coupled with the ethical considerations of conducting DDI testing in any of the aforementioned populations, PBPK models are often used to bridge the gap between clinical trials in healthy volunteers and expected outcomes in other populations. For example, PBPK models have been used to predict DDI outcomes for drugs such as solithromycin, guanfacine, risdiplam and ivabradine, with differences being noted between pediatric and adult populations (Li et al, 2018;Cleary et al, 2021;Lang et al, 2021;Salerno et al, 2021). However, while the use of PBPK modeling to predict drug exposure in pediatric populations has become relatively common, aside from the aforementioned examples, the use of PBPK modeling to predict DDI in pediatric populations lags behind that in adult populations (Templeton et al, 2018;Bi et al, 2019;Lang et al, 2021).…”
Section: Pbpk Modeling Of Ddi In Special Populationsmentioning
confidence: 99%
“…The ontogeny of P450 enzymes varies with enzyme, varying from those enzymes expressed in fetal tissue and not in adults (CYP3A7), enzymes that are expressed in adults but are considered negligible in the fetus (CYP1A2, CYP2C9, CYP2D6, CYP2E1 and CYP3A4), or those considered relatively constant from birth through to adulthood (CYP2B6, CYP2C19, CYP3A5) (Hines, 2013;Emoto and Johnson, 2022). While the proper incorporation of CYP3A7 in PBPK models has received significant attention with pediatric PBPK models given its expression in fetal tissues and neonates and not in the adult population, it should be noted that the ontogeny of many drug metabolizing enzymes needs to be accounted for (Salerno et al, 2021). Perhaps equally as important is properly accounting for the ontogeny of CYP3A4, which has been suggested to either reach adult levels between 2 to 3 years post birth or actually exceed adult levels between birth and 11 years post birth and accounted for as such in various PBPK models (Salem et al, 2014;Upreti and Wahlstrom, 2016).…”
Section: Pbpk Modeling Of Ddi In Special Populationsmentioning
confidence: 99%